The Impact of Fartlek Training on Endurance and Speed Development in Amateur Futsal Players - Muslim, Kalimasada Akbar; Himawan, Agus; Handayani, Heni Yuli; Purwoto, Septyaningrum Putri; Widodo, Haryo Mukti (Universitas Negeri Surabaya, 2025)
Purpose: This study aims to evaluate the impact of the fartlek training program on improving endurance and speed in futsal players. Materials and Methods: This quasi-experimental study involved 13 male futsal players (ages 18–25) from the Elano Futsal Team, selected through purposive sampling. Participants underwent a six-week Fartlek training program with three sessions per week. Endurance was assessed using the Multi-Stage Fitness Test (MFT), while speed was measured with a 20-meter sprint test. A paired sample t-test (p < 0.05) was used to analyze pre-test and post-test differences, with descriptive statistics (mean and standard deviation) summarizing the results. Result: The one-sample t-test results indicate a significant improvement in both endurance and speed following the six-week Fartlek training program. The post-test VO₂max scores (M = 40.46, p < 0.05) showed a statistically meaningful increase compared to pre-test scores (M = 35.29). Similarly, sprint speed improved, with post-test times (M = 2.03, p < 0.05) demonstrating a significant reduction from pre-test values (M = 2.05). Conclusion: In conclusion, Fartlek training is an effective method for improving the physical condition of futsal players, particularly their endurance and speed.